2009
DOI: 10.1017/s1743921310009385
|View full text |Cite
|
Sign up to set email alerts
|

Constraints on turbulent pressure in the X-ray halos of giant elliptical galaxies from resonant scattering

Abstract: Abstract. The dense cores of X-ray emitting gaseous halos of large elliptical galaxies with temperatures below about 0.8 keV show two prominent Fe XVII emission features, which provide a sensitive diagnostic tool to measure the effects of resonant scattering. We present here highresolution spectra of five bright nearby elliptical galaxies, obtained with the Reflection Grating Spectrometers (RGS) on the XMM-Newton satellite. The spectra for the cores of four of the galaxies show the Fe XVII line at 15.01 Angstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2009
2009

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Following up the work by Xu et al (2002);Werner et al (2009) analyzed the XMM-Newton RGS data of five nearby bright elliptical galaxies and found that the Fe xvii lines in the cores of four galaxies show evidence for resonance scattering in the innermost region. The data for NGC 4636 in particular allowed the effects of resonant scattering to be studied in detail.…”
Section: Diagnostics Of Cluster Mergersmentioning
confidence: 99%
See 2 more Smart Citations
“…Following up the work by Xu et al (2002);Werner et al (2009) analyzed the XMM-Newton RGS data of five nearby bright elliptical galaxies and found that the Fe xvii lines in the cores of four galaxies show evidence for resonance scattering in the innermost region. The data for NGC 4636 in particular allowed the effects of resonant scattering to be studied in detail.…”
Section: Diagnostics Of Cluster Mergersmentioning
confidence: 99%
“…The data for NGC 4636 in particular allowed the effects of resonant scattering to be studied in detail. Werner et al (2009) used deprojected density and temperature profiles obtained by Chandra to model the radial intensity profiles of the strongest resonance lines, accounting for the effects of resonant scattering, for different values of the characteristic turbulent velocity. Comparing the model to the Fig.…”
Section: Diagnostics Of Cluster Mergersmentioning
confidence: 99%
See 1 more Smart Citation